Evaluation of DNA polymorphisms amplified by arbitrary primers (RAPD) as genetically associated elements to differentiate virulent and non-virulent Paracoccidioides brasiliensis isolates - Motta, Teresa R.; Moreira-Filho, Carlos A.; Mendes, Rinaldo Poncio [UNESP]; Souza, Lenice R. [UNESP]; Sugizak, Maria F. [UNESP]; Baueb, Sonia; Calich, Vera L.G.; Vaz, Celideia A.C. (My University, 2002)
Randomly amplified polymorphic DNA (RAPD) analysis of 35 Paracoccidioides brasiliensis isolates was carried out to evaluate the correlation of RAPD profiles with the virulence degree or the type of the clinical manifestations of human paracoccidioidomycosis. The dendrogram presented two main groups sharing 64% genetic similarity. Group A included two isolates from patients with chronic paracoccidioidomycosis; group B comprised the following isolates showing 65% similarity: two non-virulent, six attenuated, five virulent, eight from patients with chronic paracoccidioidomycosis and two from patients with acute paracoccidioidomycosis. The virulent Pb18 isolate and six attenuated or non-virulent samples derived from it were genetically indistinguishable (100% of similarity). Thus, in our study, RAPD patterns could not discriminate among 35 P. brasiliensis isolates according to their differences either in the degree of virulence or in the type of the clinical manifestation of this fungal infection. © 2002 Federation of European Microbiological Societies. Published by Elsevier Science B.V. All rights reserved.
Keywords: Arbitrary primers; DNA polymorphism; Paracoccidioides brasiliensis; Randomly amplified polymorphic DNA; Virulent isolates; fungal DNA; primer DNA; controlled study; fungal gene; fungus identification; fungus isolation; gene amplification; gene sequence; genetic association; human; mycosis; nonhuman; priority journal; random amplified polymorphic DNA; sequence homology; virulence; Animals; DNA Primers; DNA, Fungal; Humans; Mice; Paracoccidioides; Paracoccidioidomycosis; Polymorphism, Genetic; Random Amplified Polymorphic DNA Technique; Virulence